2021
DOI: 10.1111/epi.16893
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy surgery: Late seizure recurrence after initial complete seizure freedom

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 44 publications
1
22
0
2
Order By: Relevance
“…Early studies by Rasmussen 18 described long‐term surgical outcome, noting 13% of "nontumoral" (median follow‐up = 12 years) and 6% of "tumoral" cases (median follow‐up = 8 years) experienced occasional seizures after at least 3 years free of seizures postsurgery. Late recurrences between 5 and 10 years postsurgery have been described in more recent cohorts 2,5,6,14,17,19,20 . There are few detailed data available relevant to the period after 10 postoperative years, although first recurrences after this time have been noted 2,14,21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies by Rasmussen 18 described long‐term surgical outcome, noting 13% of "nontumoral" (median follow‐up = 12 years) and 6% of "tumoral" cases (median follow‐up = 8 years) experienced occasional seizures after at least 3 years free of seizures postsurgery. Late recurrences between 5 and 10 years postsurgery have been described in more recent cohorts 2,5,6,14,17,19,20 . There are few detailed data available relevant to the period after 10 postoperative years, although first recurrences after this time have been noted 2,14,21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that most individuals who undergo resection of their seizure focus attain seizure freedom or significant reduction in seizures after surgery 1 . Unfortunately, for some individuals, the seizure freedom experienced in the first few years after surgery may not be maintained, with late seizure recurrence reported in a number of studies 2–6 . This outcome is potentially devasting, as many individuals have made a new life 7 and may believe surgery has cured their epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Bartolomei et al 21 observed, when comparing different subtypes of TLE (including TS epilepsies), a relationship between the duration of epilepsy and the extent of the epileptogenicity, thus suggesting a progressive recruitment of epileptogenic structures in human brain. Conversely, in a series including mainly lesional patients, 22 late recurrences were explained by the presence of epileptogenic networks not detected preoperatively as well by the incomplete resection of the epileptogenic lesion. In a recent study 23 combining clinical variables with brain connectome-derived features to predict seizure outcome, long-term seizure relapse was not specifically related to parameters predicting short-term outcome, thus suggesting different mechanisms In our analysis of associations, we found that undergoing TPE surgery was associated with better seizure outcome in both the short and long term in temporal plus patients.…”
Section: T a B L E 1 Univariate And Multivariate Population Average L...mentioning
confidence: 77%
“…Although we report a fairly robust mean follow-up duration of 3.6 years across the included literature, seizure recurrence can occur 5 years or more after surgery. 61 Furthermore, although concomitant FCD seems to reduce the efficacy of ECoG-guided resection, only a single study in the meta-analysis group examined this patient population. Given this, further study of these most challenging cases of MRE should be performed.…”
Section: Discussionmentioning
confidence: 99%